The forest of symbols: Aspects of ndembu ritual - Turner, Victor (London Cornell University Press, 1970)
A pioneering work of high quality, this collection of anthropological studies provides one of the most detailed records available for an African society$1 (Bor indeed for any group$1 (Bof the semantics of ritual symbolism. It combines unusually detailed ethnographic description, based upon field work among the Ndembu of Zambia, with remarkable theoretical sophistication. Professor Turner describes the ritual phenomena in terms both of practice and of their sociological and psychological implications within a preliterate society.s